The Influence of Managerial Practices and Job-Related Characteristics on Employee Perceptions of Service Quality and Turnover Intention. Issue 1 (April 2019) - Martinez, J. Michael; Barnhill, Christopher; Otto, Marcella; Mosso, Allison
Previously university recreation as an industry has focused on service quality as a means of improving customer satisfaction and loyalty. While these are important outcomes, prior research has primarily examined this from the customer's perspective. However, university recreation organizations should also pay attention to employees' perceptions of service quality and the eventual effects. In this aim, the present study examined employees' perceptions of service quality and related managerial practices within the university recreation context. Survey data were collected from both part-time and full-time employees at university recreation departments throughout various regions, measuring turnover intention, employees' perception of service quality, and managerial practices. Results indicate that managerial practices of training and empowerment significantly influenced employees' perceptions of service quality, while rewards did not. Building from these findings, university recreation should engage employees, both students and professional staff, through customer service training and empowerment in efforts to improve and sustain service quality.